Sustainable tourism practices in regional dimension (Economics and region, 2024)
The key role of tourism development on the basis of sustainability is emphasized. The ecological component is highlighted as an integral part of sustainable tourism. Sustainable development in the field of tourism emphasizes the need for effective and rational interaction between all participants in the market, since the analysis of sustainable development covers the process of preserving and reproducing the nation's genetic fund, ensuring rights and freedoms, environmental protection, creating conditions for the restoration of the biosphere and its local ecosystems, reducing anthropogenic. Impact on the environment and harmonization of development. Successful sustainable tourism practices development was studied on the example of environmental territories, cities, regions, countries of the European Union. The directions of implementation of sustainable tourism practices development of tourism were established: nature protection, management of sustainable tourism, involvement of local community, cooperation with other communities, development of places and accessibility, sustainable management of energy and resources, digitalization, struggle and adaptation to climate change. It is determined that today, the introduction of new initiatives in tourism requires a comprehensive and systematic approach with the involvement of different groups of stakeholders, especially residents of the region, because overtourism have a negative impact of residents. Sustainable tourism practices development today include investments in local communities for the formation of modern manufacturers of tourist services; development of ecological tourism through the travel of nature conservation areas; development of rural tourism through vacation in small cities in estates; popularization of cultural tourism, including historical, cultural, gastronomic and guilty, etc.; introduction of digital tools for energy-saving use of resources, complex promotion of destinations on all digital platforms, etc.; marketing campaigns aimed at raising a responsible tourist. The loss of tourism from war in Ukraine has been investigated. It is emphasized that even in the war, Ukraine has the potential for the implementation of European experience in the development of sustainable tourism.
Keywords: sustainable tourism; overtourism; sustainable tourism practices; regional dimension; European Union; Ukraine